Clinical spectrum and management of pseudoexfoliation syndrome: A cross-sectional study - Bhargavi Parth,; Margi Panchal, (Asian Journal of Medical Sciences, 2024)
Background: Pseudoexfoliation is one of the most common causes of secondary open-angle glaucoma worldwide. The current investigation is being carried out to investigate the clinical characteristics associated with pseudoexfoliation syndrome. Aims and Objectives: The current study was conducted with the goal of documenting the prevalence of the ocular clinical profile of patterns in patients with pseudo-exfoliative material attending a tertiary care hospital’s general ophthalmology outpatient department. Materials and Methods: In the current study, 100 individuals were explored who were diagnosed with pseudoexfoliation and attended the outpatient department of ophthalmology, medical college, and hospital. The Snellen chart for visual acuity was used to test visual acuity. Pseudoexfoliation glaucoma was identified based on slit lamp examination of pseudoexfoliative material, intraocular pressure (IOP) >21 mmHg, glaucomatous cupping on fundus examination, pigmentation of trabecular meshwork on gonioscopy, and glaucomatous field abnormalities on perimetry. Results: The age range of 61–70 years had the most cases of pseudoexfoliation, accounting for 23, followed by 51–60 years with 17 occurrences. The current study comprised 48 patients, 20 of whom had bilateral pseudoexfoliation and 28 of whom had unilateral pseudoexfoliation. Our findings revealed that 17 patients had high IOP. We discovered 15 cases of open-angle glaucoma and 2 cases of narrow-angle glaucoma after analyzing 48 patients. The sample of 15 individuals with open-angle glaucoma included 11 men and 4 women. Conclusion: Pseudoexfoliation becomes more common as people age, and it is often unilateral at first but progressively progresses to bilateral pseudoexfoliation, necessitating frequent follow-up in unilateral cases. Pseudoexfoliation is associated with an increased risk of glaucoma, and the majority of cases have open angles.